2018
DOI: 10.1155/2018/2410206
|View full text |Cite
|
Sign up to set email alerts
|

Towards Accurate Deceptive Opinions Detection Based on Word Order-Preserving CNN

Abstract: Nowadays, deep learning has been widely used. In natural language learning, the analysis of complex semantics has been achieved because of its high degree of flexibility. The deceptive opinions detection is an important application area in deep learning model, and related mechanisms have been given attention and researched. On-line opinions are quite short, varied types and content. In order to effectively identify deceptive opinions, we need to comprehensively study the characteristics of deceptive opinions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 19 publications
(21 reference statements)
0
12
1
2
Order By: Relevance
“…Furthermore, in mixed-domain, CNN performed better than LSTM. Motivated by this, Zhao, et al [16] introduced a word order-preserving CNN method for detecting fake reviews. They used word 2vec and the word order reserving pooling method rather than the original max pooling to generate a word vector.…”
Section: ) Convolutional Neural Network (Cnn) In Detecting Fake Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in mixed-domain, CNN performed better than LSTM. Motivated by this, Zhao, et al [16] introduced a word order-preserving CNN method for detecting fake reviews. They used word 2vec and the word order reserving pooling method rather than the original max pooling to generate a word vector.…”
Section: ) Convolutional Neural Network (Cnn) In Detecting Fake Reviewsmentioning
confidence: 99%
“…In contrast, CNN was a more efficient model for classifying short text reviews. CNN had a shorter training time, while RNN was more efficient for long texts [16]. However, the handannotated technique requires a lot of manpower.…”
Section: ) Convolutional Neural Network (Cnn) In Detecting Fake Reviewsmentioning
confidence: 99%
“…CNN based models. Zhao et al [179] suggested a CNN model for deceptive opinion spam detection. The proposed model extended the CNN with word order preserving pooling layer, which allows to keep the order of words in a sentence while analyzing deceptive opinion spam.…”
Section: Applicationmentioning
confidence: 99%
“…Bu sayede sinema filmi veya benzeri ürünler için yapılan yorumların polarizasyonu sağlanmıştır. Her iki yaklaşımın kıyaslaması da ek olarak yapılmıştır (Singh, 2014 (Zhao, 2018).…”
Section: Giriş (Introduction)unclassified
“…İlgili çalışmaların anlatıldığı kısımda da ifade edildiği üzere, Zubrinic'in 2018'de yayınladığı tüketici Duygu analizi çalışmasının, ikili (binary) bir veride elde ettiği doğruluk oranı maksimum %84,5 civarında kalmıştır (Zubrinic, 2018). Bunun yanında Zhao ve Xu'nun detaylarının yukarıda verildiği, 2018'de yayınlanan fikir tespiti (opinion detection) çalışmasında, modellerin doğruluk oranları en iyi %70,02 civarında kalmıştır (Zhao, 2018).…”
unclassified